The Effect of Adding Remifentanil to Thiopental for Anaesthesia Induction on the Success of Classic Laryngeal Mask Airway Insertion: A Randomised Double-Blind Clinical Trial † - Çakırgöz, Mensure; Demirel, İsmail; Akan, Mert; Saraç, Ömürhan; Alaygut, Ergin; Kar, Aysun Afife; Karagöz, Emre (Multidisciplinary Digital Publishing Institute (MDPI), 2025)
Background: Remifentanil, an ultra-short-acting µ-receptor agonist, is used with propofol for optimal laryngeal mask airway (LMA) insertion. However, no studies have assessed its effects when combined with thiopental on LMA conditions. The combined use of thiopental and remifentanil may offer advantages, such as enhanced cardiovascular and respiratory stability. This study aims to compare the administration of thiopental with different doses of remifentanil to assess their combined effects on LMA insertion conditions and success in a prospective, randomised double-blind study. Method: A total of 100 ASA I–II patients (18–65 years), including both male and female participants, were randomly assigned to four remifentanil dose groups (0.5–3 µg.kg?1). Induction involved thiopental (5 mg.kg?1) after remifentanil. LMA insertion conditions were evaluated using a six-variable scale. Systolic arterial pressure (SAP), diastolic arterial pressure (DAP), mean arterial pressure (MAP), heart rate (HR), and bispectral index monitor (BIS) values, as well as apnoea duration, eyelash reflex loss time, and insertion attempts, were recorded at baseline, before insertion, and at 5 min post-insertion. Results: Time to eyelash reflex loss and LMA insertion were shorter in Groups III and IV than in Groups I and II (p < 0.001). Apnoea duration was longest in Group IV, followed by Group III (p < 0.001). Groups III and IV had significantly better LMA placement, mouth opening, and ease of insertion (p < 0.05). Coughing and gagging were highest in Group I (p < 0.001). SAP, MAP, HR, and DAP were significantly lower in Group IV at various time points (p < 0.05). HR was significantly higher in Group I compared to Groups II and III at multiple time points (p < 0.05). Conclusions: The administration of 5 mg.kg?1 thiopental with 2 ?g.kg?1 remifentanil has been found to provide a stable haemodynamic response and 96% excellent or satisfactory laryngeal mask insertion conditions without increasing the duration of apnoea. © 2025 by the authors.
Keywords: anaesthetic induction; laryngeal mask airway; remifentanil; thiopental